“Silent Cancer Threat” in the Policymakers' Agenda setting In Iran - Ali Imani (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2019)
The purpose of the present study is to explain the silent threatening points in national macro policy in Iran and how these threatening issues are included in the policy calendar of policy makers. Iran's policy system seems to be influenced by normative, democratic approaches, scientific achievements and stakeholder interests in the "political calendar" section. Destructive threats are introduced into the system, which may be supported by the system itself with civil society, and the main focus of the research is to explain how these dormant cancers are activated and to propose a policy to address them. Theoretical Framework The present research is the theory of functional systems. Using a causal explanation research method, the researcher explains how social threats can be activated by unnecessary policy interventions. The researcher uses the library method and documents to explain how threatening social issues are entered into the policy calendar of policy makers and causal relations of policy interventions and activation of potential threats in Iran. The problem-solving strategy is “problem pathology” and "the legal administrative" view to problem to provide a solution. An important solution to the problem is also institutional refinement.